2013
DOI: 10.1002/bjs.9307
|View full text |Cite
|
Sign up to set email alerts
|

Value of peritoneal cytology in potentially resectable pancreatic cancer

Abstract: CY+ status is not clinically equivalent to gross peritoneal metastasis in patients with pancreatic cancer. Curative resection is still recommended regardless of CY status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 23 publications
2
41
0
Order By: Relevance
“…Previously, CY+ was associated with high pre-operative CA19-9 levels [12], larger tumors [12, 13, 15, 20, 25], tumor location in the body/tail of the pancreas [12, 13, 26], lymph node metastasis [12], vascular invasion [11], serosal invasion [15, 16] and late TNM stage [13, 26]. Our results showed that CY+ was more frequent in advanced resectable pancreatic cancer patients and was significantly associated with larger tumor size (OR 11.65, P = 0.001), tumor located in pancreatic head (OR 0.37, P = 0.000), serosal invasion (OR 3.89, P = 0.000), portal vein invasion (OR 1.82, P = 0.016), lymph vessel invasion (OR 2.71, P = 0.026), T stage (OR 2.65, P = 0.037) and N stage (OR 2.34, P = 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, CY+ was associated with high pre-operative CA19-9 levels [12], larger tumors [12, 13, 15, 20, 25], tumor location in the body/tail of the pancreas [12, 13, 26], lymph node metastasis [12], vascular invasion [11], serosal invasion [15, 16] and late TNM stage [13, 26]. Our results showed that CY+ was more frequent in advanced resectable pancreatic cancer patients and was significantly associated with larger tumor size (OR 11.65, P = 0.001), tumor located in pancreatic head (OR 0.37, P = 0.000), serosal invasion (OR 3.89, P = 0.000), portal vein invasion (OR 1.82, P = 0.016), lymph vessel invasion (OR 2.71, P = 0.026), T stage (OR 2.65, P = 0.037) and N stage (OR 2.34, P = 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact of CY+ on long-term survival of pancreatic cancer was uncertain. Some surgeons from Japan believed that CY+ status in the absence of other distant metastasis was not a contraindication for radical surgery and that surgical resection offered a chance for long-term survival [15, 16, 20, 25]. In contrast, other studies suggested that patients with CY+ experienced peritoneal recurrence and poor survival time inspite of radical surgery and adjuvant chemotherapy [1114].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with MA diagnosed by peritoneal washing cytology alone in curative intent surgery or those with recurrent pancreatic cancer after curative surgery were excluded. 12 This study was approved by the ethical committee at the University of Tokyo Hospital.…”
Section: Patientsmentioning
confidence: 99%
“…Most patients with pancreatic cancer are diagnosed at an advanced stage, with a 5‐year survival rate of less than 5% and a median survival of less than 12 months . Unfortunately, even in patients who undergo radical resection and adjuvant chemotherapy, pancreatic cancer frequently relapses, mainly in the liver, peritoneum, lymph nodes, or remnant pancreas, within 2 years after radical surgery . As for the systemic chemotherapy for metastatic or locally advanced pancreatic cancer, gemcitabine monotherapy has long been the standard treatment despite its modest survival benefit .…”
Section: Introductionmentioning
confidence: 99%